Talking is Silver, Doing is Gold? – The Influence of Corporate Social Responsibility on Corporate Financial Performance - Victoria Roth (Junior Management Science (JUMS), 2021)
Sustainability has become an omnipresent topic in the media and public as well as private debate. Stakeholders see the responsibility to promote sustainability with companies, pressuring them to increase their Corporate Social Responsibility (CSR). The relationship between CSR, being a means to satisfy a firm's stakeholders, and Corporate Financial Performance (CFP) is extensively debated in academics. This thesis contributes to this debate and tries to overcome measuring inaccuracies of previous studies by strictly categorizing CSR activities into CSR communication and CSR commitment. A total of 656 annual and CSR reports were examined, and variables representing these CSR activities were carefully and elaborately created, resulting in, among other things, a CSR communication breadth index, as well as an accurate assessment of communication quantity. A panel data analysis on European firms across industries over the observation period of eight years was conducted. The results reveal that only CSR communication has an influence on CFP. While standalone CSR reports and communication breadth have a positive influence, high levels of communication quantity have a negative effect.
Keywords: 650; Corporate Social Responsibility; corporate financial performance; CSR commitment; CSR communication; stakeholder theory